Pengaruh Tax Knowlegde, Tax Awareness, Public Trust dan E-System Tax Terhadap Kepatuhan Wajib Pajak Kendaraan Bermotor - Saiful Ilmi; Hasan Mukhibad (Journal of Accounting, Economics, and Business Education, 2024)
This study aims to analyze the influence of tax knowledge, taxpayer awareness, public trust, and the electronic tax system on motor vehicle tax compliance in Semarang. Motor Vehicle Tax (Pajak Kendaraan Bermotor) is a Local Revenue (Pendapatan Asli Daerah), making increased taxpayer compliance essential to optimizing regional revenue. The research was conducted using a quantitative approach and an associative method. The population in this study consists of motor vehicle taxpayers in Semarang. A sample of 100 respondents was determined using purposive sampling. The software used for data analysis includes SmartPLS 4.0 and SEM-PLS. Data were collected through questionnaires, and the analysis was carried out to examine the relationship between tax knowledge, taxpayer awareness, public trust, and the use of the electronic tax system with taxpayer compliance. The results show that tax knowledge, taxpayer awareness, public trust, and the use of electronic tax systems, such as New Sakpole, affect motor vehicle taxpayer compliance. The electronic system that facilitates tax payment processes and public trust in the government plays a key role in increasing compliance. In conclusion, optimizing the use of the electronic tax system, along with improving education and public trust in tax management, is expected to increase motor vehicle taxpayer compliance in Semarang, which in turn contributes to the improvement of regional revenue